건강신념모델을 적용한 경기지역 일부 초등학생의 구강보건행위 관련요인 분석 - 소미현; Mi Hyun So; 최혜정; Hye Jung Choi (Han'guk Ch'iwisaeng Hakhoe chi, 2013)
Objectives : The aim of the study is to investigate the health belief model affecting the oral health behavior in elementary school students by applying health belief model. Methods : Subjects were 216 elementary school students including 6th grade 103 boys and 113 girls in Gyeonggi-do from February 1 to February 28, 2013. They completed self-reported questionnaires after receiving informed consents. Results : Oral health belief model showed cues to action(20.39±3.11), benefits(19.63±3.37), self-efficacy(16.62±2.60), severity(14.53±3.94), susceptibility(14.31±4.62), and barrier(11.74±3.85). Oral health belief revealed the lower the level of barrier(p=0.004) and the higher cues to action, Benefits and self-efficacy were the best oral health behavior(p=0.000). The most influencing factors of oral health belief were self-efficacy(0.267) and Cues to action(0.239). Conclusions : Children`s oral health belief is associated with oral health behavior. Children`s self efficacy and cues to action toward oral care influenced on oral behavior. It is important to enhance the recognition toward self efficacy and cues to action by following recommended behavior and effective health educational program.